The Influence of Pricing and Digital Promotion Through Instagram on Tourists' Purchase Interest at the Haven Bali Seminyak Hotel - Suryananta, I Putu Bagus; Suastini, Ni Made; Pitanatri, Putu Diah Sastri (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study examines the effect of pricing and digital promotion through Instagram on tourist purchasing interest at The Haven Bali Seminyak. Using a quantitative method with 100 respondents, this study applies validity, reliability, multiple linear regression analysis, F test, T test, and coefficient of determination analysis. Data were processed using SPSS. The results show that pricing and digital promotion have a significant effect simultaneously and partially on tourist purchasing interest. Both variables contribute 61% to purchasing interest. Multiple linear regression analysis shows a positive effect of 0.337 for price and 0.317 for promotion. The T test produces a significance value of 0.000 <0.05 for both variables. The F test proves the significant effect of both variables together on purchasing interest with a significance level of 0.000 <0.05.